Super-hard high-toughness nano polycrystalline diamond composite material and preparation method thereof
By adding cubic carbon to the diamond, extremely hard and high-tough nano-polycrystalline diamond composites were prepared, which solved the problem of low fracture toughness of diamond products, achieved both hardness and toughness, and significantly improved the cutting efficiency and service life.
Patent Information
- Application Number
- CN202411483526.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-23
AI Technical Summary
Diamond products have low fracture toughness, which leads to prone to "crack collapse" during the cutting process, reducing cutting efficiency and service life.
By adding cubic carbon to the diamond, an extremely hard and high-tough nano-polycrystalline diamond composite was prepared. Graphene was used as a raw material and the cubic carbon and cubic diamond composite were combined under a narrow range of temperature and pressure conditions through high-temperature and high-pressure synthesis reaction.
When maintaining hardness compared to the average, the toughness is increased by 1-2 times, and the average toughness reaches 12.5MPa·m0.5, which is about 2-3 times that of a single crystal, which significantly improves the fracture toughness of diamond products.
Smart Images

Figure CN119455806A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of high-toughness and extremely hard materials, and specifically relates to an extremely hard and high-toughness nano-polycrystalline diamond composite material and a preparation method thereof. Background Art
[0002] Diamond is widely used in grinding abrasives and cutting tools due to its extremely high hardness (80-120 GPa). However, diamond has poor fracture toughness (4-6 MPa·m 0.5 ), which leads to the phenomenon of "chipping" during the cutting process, seriously reducing its cutting efficiency and service life. Therefore, how to improve the toughness of diamond products is a huge technical problem.
[0003] One method is to prepare polycrystalline diamond (NPD) through a catalyst-free high-temperature and high-pressure phase transition of graphite. Its hardness value HV≥120GPa is higher than that of traditional single crystal diamond, and NPD is isotropic. At the same time, its fracture toughness is about twice that of single crystal (K IC ≈8MPa.m 0.5 ). However, due to the inherent brittleness of diamond, the fracture toughness of NPD is still relatively low and difficult to achieve large-scale industrial application levels.
[0004] Another common method is to prepare diamond composite materials. For example, PCD is prepared by adding metal adhesives such as Ni, Co, and Fe to diamond and sintering at P = 5-6GPa, T = 1300-1700℃. Although this method enhances the toughness of diamond products to a certain extent, it greatly reduces the hardness (HV≈40GPa). In addition, PCD will generate a lot of heat during use due to friction, which will increase the temperature of the tool. The expansion coefficients of the adhesive and diamond are quite different, and high temperature destroys the bonding, resulting in easy detachment at high temperature. Therefore, PCD has poor wear resistance and thermal stability. High-temperature resistant ceramics such as B4C or c-BN with higher hardness are selected as adhesives for sintering. Compared with the products sintered with metal adhesives, the hardness is improved, but the hardness is still lower than that of single crystals (HV<80GPa), and the sintering pressure is harsh (P≥12GPa).
[0005] In summary, selecting a second phase with properties close to diamond hardness, thermal expansion coefficient and elastic modulus, and compounding it with cubic diamond to prepare diamond composites can effectively overcome the problems existing in PCD. For example, cubic diamond and hexagonal diamond composites have significantly improved toughness compared to single crystals, while their hardness is comparable to that of single crystal diamonds. Therefore, exploring new diamond composites is conducive to solving the technical problem of poor toughness of diamonds, and has broad application prospects in industrial precision cutting and other finishing processes. Summary of the invention
[0006] In order to solve the above-mentioned technical problems, the present invention provides an extremely hard and high-toughness nano-polycrystalline diamond composite material and a preparation method thereof, and prepares an extremely hard and high-toughness nano-polycrystalline diamond composite material (cubic diamond + cubic carbon). Compared with single crystal diamond, the toughness is increased by 1-2 times while maintaining the hardness.
[0007] The invention provides an extremely hard and high-tough nanometer polycrystalline diamond composite material, which consists of cubic phase diamond and cubic carbon, wherein the molar percentage of the cubic phase diamond is 70-90%, and the molar percentage of the cubic carbon is 10-30%.
[0008] Compared with the existing technology, this patent is the first to prepare a diamond composite material containing cubic carbon, and the prepared diamond composite material has a hardness greater than 120GPa and an average toughness of 12.5MPa·m 0.5 , about 2-3 times that of single crystal.
[0009] In some embodiments, the ultra-hard and high-toughness nano-polycrystalline diamond composite material has a Vickers hardness of 120-150 GPa and a fracture toughness of 12-15 MPa·m 0.5
[0010] The second object of the present invention is to provide a method for preparing an extremely hard and high-toughness nano-polycrystalline diamond composite material, which specifically includes the following steps: using graphene as a raw material, pre-pressing the graphene into a cylinder in a mold, subjecting the pre-pressed sample to a high-temperature and high-pressure synthesis reaction, and cooling and releasing the pressure after the high-temperature and high-pressure synthesis reaction to obtain an extremely hard and high-toughness nano-polycrystalline diamond composite material.
[0011] In some embodiments, the graphene is sheet graphene.
[0012] In some embodiments, the high temperature and high pressure synthesis reaction is carried out in a Kawai large volume multi-stage anvil apparatus.
[0013] In some embodiments, the parameters of the Kawai large-volume multi-stage anvil device are as follows: hexagonal boron nitride wrapping, rhenium tube heating, and tungsten-rhenium thermocouple synchronous temperature measurement.
[0014] In some embodiments, the parameters of the high temperature and high pressure synthesis reaction are as follows: synthesis pressure is 22 GPa, temperature is 1800-2000° C., and reaction time is 30 min.
[0015] The present invention adopts the above narrow range of synthesis parameters. Experimental results show that pressure has a significant effect on the phase composition of the synthetic material, temperature has a greater effect on the ratio of the two phases in the diamond composite material, and the composite has a significant effect on the hardness and toughness.
[0016] Compared with the prior art, the present invention preferably uses graphene flakes as raw materials, utilizes its extremely thin graphite layer and high concentration of defects, and precisely controls the temperature and pressure conditions to synthesize cubic carbon and cubic diamond composite materials for the first time within a very narrow temperature and pressure range. The composite material has a fracture toughness nearly three times that of single crystal diamond and comparable hardness. This patented method overcomes the technical difficulty of the contradiction between hardness and toughness in superhard materials, and has a great promoting effect on the preparation of extremely hard and high-toughness diamond-related materials.
[0017] In some embodiments, the specific steps of cooling and decompressing are: cooling to room temperature at a cooling rate of 100° C. / min, and then decompressing. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the X-ray diffraction pattern of the cubic diamond prepared in Example 1 of the present invention.
[0019] Figure 2 This is the X-ray diffraction pattern of cubic diamond prepared in Example 2 of the present invention.
[0020] Figure 3 X-ray diffraction patterns of graphite and cubic diamond prepared in Example 3 of the present invention.
[0021] Figure 4 This is the X-ray diffraction pattern of the cubic diamond and cubic carbon composite material prepared in Example 4 of the present invention.
[0022] Figure 5 This is the X-ray diffraction pattern of the cubic diamond and cubic carbon composite material prepared in Example 5 of the present invention.
[0023] Figure 6 This is an indentation image of the cubic diamond and cubic carbon composite material prepared in Example 5 of the present invention.
[0024] Figure 7 This is the X-ray diffraction pattern of the cubic diamond prepared in Example 6 of the present invention. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.
[0026] It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0027] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.
[0028] The technical effects of the present invention are described below in conjunction with specific embodiments.
[0029] Example 1
[0030] The present embodiment provides a material, which is prepared by the following preparation method: using flake graphene as a raw material, pressing it into a cylindrical shape (diameter 2 mm, height 1 mm) using a tungsten carbide mold, wrapping it with hexagonal boron nitride, heating it with a rhenium tube, and synchronously measuring the temperature with a tungsten-rhenium thermocouple. Using a Kawai-type large-volume multi-stage anvil cell experimental device, a diamond composite material is prepared at a pressure of P = 15 GPa and a temperature of T = 2000°C, the insulation time range is 30 minutes, and the temperature is slowly reduced to room temperature at a rate of 100°C / min, and then the pressure is released.
[0031] Figure 1 is the X-ray diffraction pattern of the cubic diamond prepared in this embodiment; Figure 1 It can be seen that the main component of the material prepared in this embodiment is cubic diamond. The hardness of the sample was tested using a Vickers hardness tester. The test results show that the hardness of the material prepared in this embodiment is HV=122.4±5.8GPa, (F=19.6N), and the fracture toughness is K IC =7.6±2.8MPa.m 0.5 .
[0032] Example 2
[0033] The present embodiment provides a material, which is prepared by the following preparation method: using lamellar graphene as a raw material, pressing it into a cylindrical shape (diameter 2 mm, height 1 mm) using a tungsten carbide mold, wrapping it with hexagonal boron nitride, heating it with a rhenium tube, and synchronously measuring the temperature with a tungsten-rhenium thermocouple, using a Kawai type large-volume multi-stage anvil cell experimental device, preparing a diamond composite material at a pressure of P = 20 GPa and a temperature of T = 2000°C, the insulation time range is 30 minutes, and the temperature is slowly reduced to room temperature at a rate of 100°C / min, and then the pressure is released.
[0034] Figure 2 X-ray diffraction pattern of cubic diamond prepared in Example; Figure 2 It can be seen that the main component of the material prepared in this embodiment is square diamond. The hardness of the material prepared in this embodiment is measured by a Vickers hardness tester. The hardness is HV=123.1±5.5GPa, (F=19.6N), and the fracture toughness is K IC =8.0±1.5MPa.m 0.5 .
[0035] Example 3
[0036] The present embodiment provides a material, which is prepared by the following preparation method: using lamellar graphene as a raw material, pressing it into a cylindrical shape (diameter 2 mm, height 1 mm) using a tungsten carbide mold, wrapping it with hexagonal boron nitride, heating it with a rhenium tube, and synchronously measuring the temperature with a tungsten-rhenium thermocouple, using a Kawai type large-volume multi-stage anvil cell experimental device, preparing a diamond composite material at a pressure of P = 22 GPa and a temperature of T = 1600°C, the insulation time range is 30 minutes, and the temperature is slowly reduced to room temperature at a rate of 100°C / min, and then the pressure is released.
[0037] Figure 3 The X-ray diffraction patterns of graphite and cubic diamond prepared in this embodiment are as follows: Figure 3 It can be seen that the main components of the material prepared in this embodiment are graphite and diamond.
[0038] Example 4
[0039] The present embodiment provides a material, which is prepared by the following preparation method: using lamellar graphene as a raw material, pressing it into a cylindrical shape (diameter 2 mm, height 1 mm) using a tungsten carbide mold, wrapping it with hexagonal boron nitride, heating it with a rhenium tube, and synchronously measuring the temperature with a tungsten-rhenium thermocouple, using a Kawai type large-volume multi-stage anvil cell experimental device, preparing a diamond composite material at a pressure of P = 22 GPa and a temperature of T = 1800°C, the insulation time range is 30 minutes, and the temperature is slowly reduced to room temperature at a rate of 100°C / min, and then the pressure is released.
[0040] Figure 4 X-ray diffraction pattern of cubic diamond and cubic carbon composite material prepared in this embodiment; Figure 4 It can be seen that a new phase appears in the sample prepared in this embodiment, the main components of which are a composite phase of square diamond and cubic carbon. The hardness of the material prepared in this embodiment is measured by a Vickers hardness tester. The hardness is HV=132.9±9.3GPa, (F=19.6N), and the fracture toughness is K IC =9.8±3.4MPa.m 0.5 .
[0041] Example 5
[0042] The present embodiment provides a material, which is prepared by the following preparation method: using flaky graphene as a raw material, pressing it into a cylindrical shape (diameter 2 mm, height 1 mm) using a tungsten carbide mold, wrapping it with hexagonal boron nitride, heating it with a rhenium tube, and synchronously measuring the temperature with a tungsten-rhenium thermocouple, using a Kawai type large-volume multi-stage anvil cell experimental device, preparing a diamond composite material at a pressure of P = 22 GPa and a temperature of T = 2000°C, the insulation time range is 30 minutes, and the temperature is slowly reduced to room temperature at a rate of 100°C / min, and then the pressure is released.
[0043] Figure 5 X-ray diffraction patterns of cubic diamond and cubic carbon composite materials prepared in this embodiment; Figure 6 The indentation diagram of the cubic diamond and cubic carbon composite material prepared in this embodiment; Figure 5 It can be seen that the main components of the sample obtained in this embodiment are square diamond and cubic carbon composite phase, and Figure 4 and Figure 5 It can be seen that as the temperature increases, the cubic carbon content increases; measured using a Vickers hardness tester, the hardness of the material prepared in this embodiment is HV=128.4±5.3GPa, (F=19.6N), and the fracture toughness is K IC =12.5±2.1MPa.m 0.5 , which is about twice as much as single crystal diamond. See the indentation diagram. Figure 6 .
[0044] Example 6
[0045] The present embodiment provides a material, which is prepared by the following preparation method: using lamellar graphene as a raw material, pressing it into a cylindrical shape (diameter 2 mm, height 1 mm) using a tungsten carbide mold, wrapping it with hexagonal boron nitride, heating it with a rhenium tube, and synchronously measuring the temperature with a tungsten-rhenium thermocouple, using a Kawai type large-volume multi-stage anvil cell experimental device, preparing a diamond composite material at a pressure of P = 22 GPa and a temperature of T = 2200°C, the insulation time range is 30 minutes, and the temperature is slowly reduced to room temperature at a rate of 100°C / min, and then the pressure is released.
[0046] Figure 7 is the X-ray diffraction pattern of the cubic diamond prepared in this embodiment; Figure 7 It can be seen that as the temperature continues to increase, cubic carbon disappears and the main component of the sample is cubic diamond. The hardness is HV = 130.4 ± 10.0 GPa, (F = 19.6 N), and the fracture toughness is K IC =8.5±2.5MPa.m 0.5 .
[0047] It can be seen from Examples 1-4 that when the synthesis pressure is less than 22 GPa, the second phase of cubic carbon does not appear, and even when the pressure reaches 22 GPa, when the temperature is less than 1800°C, no cubic carbon is generated. And it can be seen from Examples 4-6 that when the pressure P = 22 GPa and the temperature is in the range of T = 1800-2000°C, a two-phase diamond composite material of cubic diamond and cubic carbon is synthesized, and the cubic carbon content first increases and then decreases with increasing temperature. When the temperature T>2000, the cubic carbon disappears, and the synthesized sample is a single phase of cubic diamond. Moreover, compared with the single phase, the fracture toughness of the diamond composite material is improved by 150% under the condition of basically the same hardness.
[0048] In summary, during the preparation process of the extremely hard and high-toughness nano-polycrystalline diamond composite material prepared by the preparation method of the present invention, pressure has a significant effect on the phase composition of the synthetic material, temperature has a greater influence on the ratio of the two phases in the diamond composite material, and the composite has a significant effect on the hardness and toughness.
[0049] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. An extremely hard and tough nano polycrystalline diamond composite material, characterized in that: The extremely hard and high-toughness nano-polycrystalline diamond composite material consists of cubic phase diamond and cubic carbon, wherein the molar percentage of the cubic phase diamond is 70-90%, and the molar percentage of the cubic carbon is 10-30%.
2. The extremely hard and high-toughness nano-polycrystalline diamond composite material according to claim 1, characterized in that: The extremely hard and high-toughness nano-polycrystalline diamond composite material has a Vickers hardness of 120-150 GPa and a fracture toughness of 12-15 MPa·m 0.5 .
3. A method for preparing the extremely hard and high-toughness nano-polycrystalline diamond composite material as claimed in claim 1 or 2, characterized in that: The preparation method specifically comprises the following steps: using graphene as raw material, pre-pressing the graphene into a cylinder in a mold, subjecting the pre-pressed sample to a high-temperature and high-pressure synthesis reaction, and cooling and releasing the pressure after the high-temperature and high-pressure synthesis reaction to obtain an extremely hard and tough nano-polycrystalline diamond composite material.
4. The method for preparing the extremely hard and high-toughness nano-polycrystalline diamond composite material according to claim 3, characterized in that: The graphene is sheet graphene.
5. The method for preparing the extremely hard and high-toughness nano-polycrystalline diamond composite material according to claim 3, characterized in that: The high temperature and high pressure synthesis reaction is carried out in a Kawai large volume multi-stage anvil apparatus.
6. The method for preparing the extremely hard and high-toughness nano-polycrystalline diamond composite material according to claim 5, characterized in that: The parameters of the Kawai large-volume multi-stage anvil device are as follows: hexagonal boron nitride wrapping, rhenium tube heating, and tungsten-rhenium thermocouple synchronous temperature measurement.
7. The method for preparing the extremely hard and high-toughness nano-polycrystalline diamond composite material according to claim 3, characterized in that: The parameters of the high temperature and high pressure synthesis reaction are as follows: synthesis pressure is 22 GPa, temperature is 1800-2000° C., and reaction time is 30 min.
8. The method for preparing the extremely hard and high-toughness nano-polycrystalline diamond composite material according to claim 3, characterized in that: The specific steps of cooling and decompression are: cooling to room temperature at a cooling rate of 100° C. / min, and then decompression.
Citation Information
Patent Citations
Novel production method for polycrystalline diamond compact (PDC) superhard material
CN103737008A
Synthesis method of composite superhard material with high fracture toughness
CN108786659A
Method for preparing nano polycrystalline diamond under low pressure without catalysts
CN109701447A
Synthesis method of carbon material with super-high hardness
CN112158835A
Preparation method of high-toughness nano polycrystalline diamond composite material
CN118405925A
Cited By
Micro-nano polycrystalline diamond composite material and preparation method thereof
CN121850666A
Cubic boron nitride-nano polycrystalline diamond composite material and preparation method thereof
CN121872777A
Hexagonal boron nitride-nano polycrystalline diamond composite material and preparation method thereof
CN121974695A